The Influence of the Tourism Sector on Labor Absorption in North Minahasa Regency - T. Tumigolung, Febbe; S.M. Engka, Daisy; Th. B. Maramis, Mauna (Formosa Journal of Applied Sciences, 2024)
With continuous growth, the travel and tourism industry has become the largest. Both North Minahasa Regency and the Indonesian economy will benefit from this. This research aims to determine the extent to which the tourism industry influences labor absorption in North Minahasa Regency. For the purposes of this research, data from 2010 to 2021 was collected from secondary sources. This research uses multiple linear regression analysis as a quantitative method. This study concludes that although the number of accommodation and eating places has a small negative impact, the number of visitors has a significant positive impact. Additionally, there is a strong inverse relationship between the quantity of tourist attractions and their overall quality. The high number of tourists in North Minahasa Regency is caused by the presence of hotels, restaurants and tourist attractions in the area, all of which have an impact on labor absorption.